2015
DOI: 10.1371/journal.pone.0140961
|View full text |Cite
|
Sign up to set email alerts
|

Primates, Provisioning and Plants: Impacts of Human Cultural Behaviours on Primate Ecological Functions

Abstract: Human provisioning of wildlife with food is a widespread global practice that occurs in multiple socio-cultural circumstances. Provisioning may indirectly alter ecosystem functioning through changes in the eco-ethology of animals, but few studies have quantified this aspect. Provisioning of primates by humans is known to impact their activity budgets, diets and ranging patterns. Primates are also keystone species in tropical forests through their role as seed dispersers; yet there is no information on how prov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(50 citation statements)
references
References 36 publications
0
50
0
Order By: Relevance
“…Even Least Concern species such as M. radiata and M. fascicularis have already suffered massive declines in their populations (Eudey, 2008; Sengupta & Radhakrishna, 2013; Singh, Erinjery, Kavana, Roy, & Singh, 2011a). In addition, studies have shown that seed dispersal by macaques can be negatively impacted when humans provide food subsidies to them (Sengupta, McConkey, & Radhakrishna, 2015). It is thus essential to maintain viable populations of macaques across their range and keep human interventions at a minimum to ensure that they continue to reliably disperse the seeds of a wide gamut of plant species in the Anthropocene.…”
Section: Discussionmentioning
confidence: 99%
“…Even Least Concern species such as M. radiata and M. fascicularis have already suffered massive declines in their populations (Eudey, 2008; Sengupta & Radhakrishna, 2013; Singh, Erinjery, Kavana, Roy, & Singh, 2011a). In addition, studies have shown that seed dispersal by macaques can be negatively impacted when humans provide food subsidies to them (Sengupta, McConkey, & Radhakrishna, 2015). It is thus essential to maintain viable populations of macaques across their range and keep human interventions at a minimum to ensure that they continue to reliably disperse the seeds of a wide gamut of plant species in the Anthropocene.…”
Section: Discussionmentioning
confidence: 99%
“…Given the globally increasing significance of human-wildlife interactions and coexistence (Barua, Bhagwat, & Jadhav, 2013;Dickman, 2010;Nyhus, 2016), and the shared ecology and evolutionary history of humans and primates (Fuentes, 2006;Fuentes & Hockings, 2010), research at human-primate interfaces has become especially significant over the past decade (Fuentes, 2006;Paterson & Wallis, 2005;Radhakrishna & Sinha, 2011;Riley, 2018). Human-primate interactions are highly diverse in form and frequency, from being neutral and/or involving little or no antagonism (e.g., mutual tolerance, provisioning, religious symbols: Radhakrishna & Sinha, 2011;Sengupta, McConkey, & Radhakrishna, 2015;reviewed in Paterson & Wallis, 2005), to visibly destructive or antagonistic (e.g., destruction of habitat, culling, mutual aggression: Borgerson, 2015;Plumptre et al, 2016;Southwick, Siddioi, Farooqui, & Pal, 1976).…”
Section: Introductionmentioning
confidence: 99%
“…Increasing food waste availability can have a similar effect; for instance, overfishing and increasing waste in landfills have changed the resource base of coastal food webs, and generalist seabirds like western gulls (Larus occidentalis) have responded by shifting their diet to human trash, but at the same time, they increased predation pressure on a threatened species of fish (steelhead, Oncorhynchus mykiss) [27]. More broadly, food provisioning by humans can alter ecosystem functions provided by opportunistic herbivores who act as seed dispersers, as in the case of human food provisioning of macaques (Macaca mulatta) which caused shorter seed dispersal ranges and dispersal into human-modified areas that were not conducive to seed germination [28].…”
Section: Indirect Effects On Other Species and Ecological Communitiesmentioning
confidence: 99%